2022
DOI: 10.1186/s12864-022-09052-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of non-coding RNA networks in infected macrophages revealing the pathogenesis of F. nucleatum-associated diseases

Abstract: Background F. nucleatum, as an important periodontal pathogen, is not only closely associated with the development of periodontitis, but also implicated in systemic diseases. Macrophages may act as an important mediator in the pathogenic process of F. nucleatum infection. As non-coding RNAs (ncRNAs) have attracted extensive attention as important epigenetic regulatory mechanisms recently, we focus on the competing endogenous RNA (ceRNA) regulatory networks to elucidate the pathogenesis of F. nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…The mapped reads were aligned on the reference sequence with the specified range sequence in miRBase to get the sRNA details for each sample match. Then, we integrated miRNAs prediction software miREvo and miR-deep2 to analyze new miRNAs [34][35][36]. For circRNA identity, we first analyzed the numbers in the CIGAR file.…”
Section: Ncrna Identitymentioning
confidence: 99%
“…The mapped reads were aligned on the reference sequence with the specified range sequence in miRBase to get the sRNA details for each sample match. Then, we integrated miRNAs prediction software miREvo and miR-deep2 to analyze new miRNAs [34][35][36]. For circRNA identity, we first analyzed the numbers in the CIGAR file.…”
Section: Ncrna Identitymentioning
confidence: 99%
“…LncRNAs TUG1 and SOX2OT have been shown to have a renoprotective effect against DN (Chen et al 2021 ; Wang et al 2021 ). Besides, lncRNA MEG3-205, NEAT1, and GAS5, have a clear opposing effect on DN by exacerbating renal fibrosis (El-Lateef et al 2022 ; Feng et al 2019 ; Zhou et al 2022 ). In addition, lncRNAs possess a secondary structure that exhibits remarkable stability in bodily fluids, including blood and urine (Smola et al 2016 ; Zhang et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study identified a series of ncRNAs related to F. nucleatum infection and associated diseases, where abnormal expression of miR-150-5p was observed, establishing it as a promising ncRNA candidate for periodontitis. 9 Previously, miR-150-5p was reported to mediate the development of human diseases, such as osteoarthritis, sepsis, and malignant tumors. [10][11][12] Additionally, miR-150-5p was also demonstrated to regulate the osteogenic differentiation of fibroblasts in ankylosing spondylitis and mediate the transition of lung fibroblast to myofibroblast.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the roles of non‐coding RNAs in regulating HGFs and some studies have been devoted to identifying biomarker candidates for periodontitis. A recent study identified a series of ncRNAs related to F. nucleatum infection and associated diseases, where abnormal expression of miR‐150‐5p was observed, establishing it as a promising ncRNA candidate for periodontitis 9 . Previously, miR‐150‐5p was reported to mediate the development of human diseases, such as osteoarthritis, sepsis, and malignant tumors 10–12 .…”
Section: Introductionmentioning
confidence: 99%